2010
DOI: 10.1007/s00125-010-1980-9
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial hyperaminoacidaemia overcomes insulin resistance of protein anabolism in men with type 2 diabetes

Abstract: Aims/hypothesis Although protein is usually ignored when considering insulin resistance, we have shown resistance of protein concurrent with glucose metabolism in men with type 2 diabetes during a hyperinsulinaemic clamp at euglycaemia and fasting aminoacidaemia. We hypothesised that this resistance is even worse during conditions that simulate the postprandial state, when anabolism should be maximal. Methods Eight overweight and obese men with type 2 diabetes underwent a hyperinsulinaemic-hyperglycaemic (8 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…These findings, together with the evidence of impaired protein metabolism in diabetes [16] that is overcome by generous protein provision [41], do not support recommendations to restrict protein intake.…”
Section: Discussionmentioning
confidence: 64%
“…These findings, together with the evidence of impaired protein metabolism in diabetes [16] that is overcome by generous protein provision [41], do not support recommendations to restrict protein intake.…”
Section: Discussionmentioning
confidence: 64%
“…We showed that amino acids can overcome the insulin resistance of protein metabolism through their anabolic action (Bassil et al, 2011a) without further impairing glucose metabolism in obese middle-aged men with type 2 diabetes (Bassil et al, 2011b). Moreover, a recent systematic review and meta-analysis of 20 randomized controlled trials investigating dietary approaches in the management of type 2 diabetes indicated that high-protein diets are among the few approaches that are effective in improving glycemic control (Ajala et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…The [ 2 H 5 ]phenylalanine infusion started 1.5 h before the other isotopes, then all continued for 6 h, with clamp from 4.5 to 7.5 h with: human insulin (primed, then 0.98‐1.3 mU [kg FFM −1 ] min −1 , Humulin R; Eli Lilly Canada Inc, Toronto, ON, Canada); octreotide (35.3 ng [kg FFM −1 ] min −1 , Omega, Montreal, QC, Canada); glucagon (0.94 ng [kg FFM −1 ] min −1 , Eli Lilly); and human growth hormone (hGH; 3.53 ng [kg FFM −1 ] min −1 , Saizen, EMD Serono, Canada). Concurrently, 20% low‐enriched 1 3 C‐glucose (Avebe b.a., Foxhol, Netherlands) and 10% AA solution (TrophAmine, B. Braun Medical, Irvine, CA) were infused at variable rates to clamp glucose at 8 mmol l −1 and branched‐chain amino acids (BCAA), at postprandial concentrations , both based on 5‐min interval measurements. Blood was collected hourly for substrates, hormones, and isotopic enrichment and at 10‐min intervals from 2.5‐3 h to 5.5–6 h. L‐[1‐ 13 C] leucine kinetics were calculated using plasma 1‐[ 13 C] α‐ketoisocaproic acid (KIC) enrichment (reciprocal model) .…”
Section: Methodsmentioning
confidence: 99%